Law Enforcement Agencies in the Field of Economic Security: Ukrainian Realities and Perspectives (Law and Safety, 2020)
It has been noted that there is currently no single law enforcement agency in the field of economic security in Ukraine, the relevant functions and powers are scattered between different law enforcement agencies, which causes low efficiency of their activities and difficulties in cooperation. The topical problems of functioning of law enforcement agencies of Ukraine in the field of economic security have been studied and practical recommendations concerning reforming the system of law enforcement agencies of Ukraine in this sphere have been developed.To achieve the purpose of the study, the author has used general scientific and special research methods: formal and legal method – during the study of the functions and powers of law enforcement agencies in the field of economic security; analogy, method of causal analysis, situational and prognostic methods – for the analysis of the draft Law “On the Bureau of Economic Security of Ukraine” No. 3087-d.Analyzing, systematizing and generalizing normative and scientific sources, the author has researched the main functions and powers of law enforcement agencies of Ukraine in the field of economic security. Problems related to the functioning of several law enforcement agencies in this area have been identified. The necessity of creation of a single law enforcement agency in the field of economic security in Ukraine has been substantiated. The draft Law “On the Bureau of Economic Security of Ukraine” No. 3087-d, approved by the Verkhovna Rada of Ukraine in the first reading, has been analyzed; the author has provided recommendations for its improvement.The author has elaborated propositions to reform the law enforcement system of Ukraine in the field of economic security of the state, in particular recommendations for improving the draft Law “On the Bureau of Economic Security of Ukraine” No. 3087-d.It has been noted that the practical significance of the obtained results lies in the use of conclusions and recommendations in the activities of public authorities in the process of carrying out their legislative and regulatory functions.
Keywords: economic security of the state; law enforcement agencies; National Police; Security Service of Ukraine; Tax Police; National Anti-Corruption Bureau of Ukraine; reform of law enforcement agencies; Bureau of Economic Security